ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN BIOLOGI - Desi Nuzul Agnafia (Florea : Jurnal Biologi dan Pembelajarannya, 2019)
The purpose of this research are to analyze the critical thinking ability of XA grade student at SMK BIM Ngawi. This research is include of descriptive qualitative research. The subject of research is XA grade at SMK BIM Ngawi. The technique sampling is purposive samping. The technique that use to fix the data is essay written test that developed by critical thinking ability indicator, based on Facione opinion. Based on data analysis critical thinking ability is gotten average explanation score 72% high category, interpretation 63% high category, analysis 31% low category, self regulation 51% category enough, evaluation 46% category enough and inferation 62% high category. The results or research show that almost the students critical thinking ability category enough. That result give an information to the teacher to train the criical thinking ability so can improve the students critical thinking ability more.